2021
DOI: 10.3928/19404921-20210325-02
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Interventions Promoting Social Support and Interaction Among Older Adults: A Systematic Review

Abstract: Tai chi is known to improve balance and reduce falls in older adults. Yet, little is known about the impact of group tai chi on perceived social support and its relationship with participant self-efficacy and adherence. The current systematic review, guided by Social Cognitive Theory and Successful Aging, includes an overview of tai chi interventions with and without enhancements (e.g., music, mentorship, group practice) that evaluated social support among their outcomes ( N = 10). PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Based on the distance to zero, determine whether a collision has occurred. However, the biggest feature of GJK algorithm is that the input set of vertex will not be any direct operation calculation, but by calculating the Minkowski distance between two objects, thus calculating the distance between two convex problems into solving a convex set to the origin of the minimum distance problem [21].…”
Section: Problems Existing In the Inheritance And Disseminationmentioning
confidence: 99%
“…Based on the distance to zero, determine whether a collision has occurred. However, the biggest feature of GJK algorithm is that the input set of vertex will not be any direct operation calculation, but by calculating the Minkowski distance between two objects, thus calculating the distance between two convex problems into solving a convex set to the origin of the minimum distance problem [21].…”
Section: Problems Existing In the Inheritance And Disseminationmentioning
confidence: 99%
“…The study results confirmed H2, which indicates a significant mediating effect of social participation between tai chi, ba duan jin, walking, and the mental health status of urban older adults living alone. Tai chi interventions among older adults have been shown to increase social support and promote social participation ( 68 ), while higher levels of social participation are linked to lower levels of psychological disorders ( 69 ). In other words, social participation improves mental health, and engaging in social activities can consistently contribute to an individual’s well-being in later life ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tai Chi contributes to improved aerobic capacity, positively impacts cardiovascular risk factors, and lowers blood pressure 14 . Moreover, its versatility allows it to be practiced individually or in group settings, making it accessible to individuals with busy lifestyles and fostering social engagement 15 . Furthermore, Tai Chi requires no special equipment and can be enjoyed by virtually anyone, anywhere 16 .…”
Section: Introductionmentioning
confidence: 99%